2022
DOI: 10.1016/j.envres.2022.112921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental parameters and their interactions on the spreading of SARS-CoV-2 in North Italy under different social restrictions. A new approach based on multivariate analysis

Abstract: In 2020 North Italy suffered the SARS-CoV-2-related pandemic with a high number of deaths and hospitalization. The effect of atmospheric parameters on the amount of hospital admissions (temperature, solar radiation, particulate matter, relative humidity and wind speed) is studied through about 8 months (May–December). Two periods are considered depending on different conditions: a) low incidence of COVID-19 and very few regulations concerning personal mobility and protection (“free/summer period”); b) increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 157 publications
(225 reference statements)
0
6
0
1
Order By: Relevance
“…Solar irradiance can also limit the spread of SARS-CoV-2, with fewer cases reported in regions with higher temperatures and stronger solar radiation [ 34 ]. While the number of cases exhibits a weakly positive correlation with barometric pressure, precipitation, diurnal temperature, sulfur dioxide, and ozone [ 35 ], wind speed is rarely significantly associated with the number of infected people, with exceptions such as decreased numbers during intense windy days [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Solar irradiance can also limit the spread of SARS-CoV-2, with fewer cases reported in regions with higher temperatures and stronger solar radiation [ 34 ]. While the number of cases exhibits a weakly positive correlation with barometric pressure, precipitation, diurnal temperature, sulfur dioxide, and ozone [ 35 ], wind speed is rarely significantly associated with the number of infected people, with exceptions such as decreased numbers during intense windy days [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Those studies have initially established relationships between air pollutants and COVID- 19 transmission, particularly PM 2 . 5 ( Wang et al, 2020 ; Tateo et al, 2022 ), but also PM 10 , CO, NO 2 , and O 3 ( Zhu et al, 2020 ; Copat et al, 2020 ). Many mortality studies have been performed worldwide ( Bozack et al, 2022 ; Coker et al, 2020 ; Hendryx and Luo, 2020 ; Wu et al, 2020 ), but only a few studies contemplating a short term analysis ( Jiang and Xu, 2021 ; Khorsandi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The entire dataset ranged from 8 to 6238 ng/ml. Nevertheless, several studies have explored ferritin as a potential target for the treatment of COVID-19 and, 66 iii) In March 2020, since the earliest phases of SARS-CoV-2 pandemic outbreak, the rationale for a possible protective and therapeutic role of vitamin D and other micronutrients was proposed by Fiorino and other authors, 5,25,32,68 on the basis of the possible ability of some fat-soluble compounds, in modulating directly or indirectly the replication of SARS-CoV-2, in regulating host's immune activity against this pathogen and, probably, in improving his response to vaccination. 69 Since then, a large series of retrospective and prospective trials and systematic reviews have been carried out in patients suffering from COVID-19 with the aim to assess the potential association between their vitamin D levels and their disease outcome as well as the impact of vitamin D supplementation on their prognosis.…”
Section: Laboratory Parametersmentioning
confidence: 99%
“…Immune-compromised patients, such as individuals with cancer or with persistent pathological conditions, as well as elderly subjects with several diseases, including diabetes, hypertension, cardiovascular disease, obesity, autoimmune diseases, chronic kidney/lung/liver diseases, dementia, solid organ transplant 22,23 are at higher risk to develop severe forms of COVID-19 with a potentially poor outcome in comparison to younger and healthier individuals. 24,25 SARS-CoV-2 infection may cause an impairment in the function of kidney and gastrointestinal tract, mainly in elderly people, [26][27] inducing fluid and electrolyte imbalances (such as hyper/hyponatremia, hypokalemia, hypocalcemia) in those subjects who undergo a higher probability of complications and even a more elevated risk of death. [28][29][30][31] Furthermore, it has been suggested that low levels of vitamin D are associated with an increased risk of SARS-CoV-2 infection and a poorer prognosis in patients with deficiency of this micronutrient, but to date, no definitive results have been yet obtained.…”
Section: Introductionmentioning
confidence: 99%